2019
DOI: 10.37358/rc.19.5.7209
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Role of Biochemical Plasma Factors in Patients with Severe Traumatic Brain Injuries

Abstract: Traumatic brain injuries (TBI) represent a high impact public health problem due to a high rate of death , long term disability and occurrence especially in young adults. Despite several promising animal studies, several parameters were proposed as biological markers and were assessed for this aim. Our study proposes the study of the early biochemical changes in association to hematological parameters for severe TBI patients prognosis. 43 patients with acute TBI were included in study based on clinical, labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Other studies have shown that SA represents a cardiovascular risk factor, as it is associated with increased cardiovascular mortality (10) and cerebrovascular disease (8,11). In addition, it has been demonstrated that SA levels are elevated in patients with type I and II diabetes mellitus, therefore it is assumed that SA could be associated with insulin resistance or hyperinsulinemia (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown that SA represents a cardiovascular risk factor, as it is associated with increased cardiovascular mortality (10) and cerebrovascular disease (8,11). In addition, it has been demonstrated that SA levels are elevated in patients with type I and II diabetes mellitus, therefore it is assumed that SA could be associated with insulin resistance or hyperinsulinemia (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…Na + is also involved in the neuromuscular excitability and in the polarization and depolarization of the cellular membrane (action potential), opposing the potassium effects. The normal range of serum Na + in adults are: 135-145 mmol/l (135-145 mEq/l) ( 3 ) and its variations could be used as predictors of prognosis in other pathologies ( 4 , 5 ).…”
Section: Sodium (Na + )mentioning
confidence: 99%
“…Tinnitus can be a prediction factor of a state of neuronal hyperactivity that is in standby conditions. Thus, nonpulsatile tinnitus may be an indirect marker of the risk of disease relapse, while pulsatile tinnitus indicates a stroke risk [36][37][38].…”
Section: Pharmacological Clinical Stages Of the Dopaminergic Modelmentioning
confidence: 99%